The genomic basis of adaptation to high‐altitude habitats in the eastern honey bee (Apis cerana). Issue 4 (4th February 2019) - Montero‐Mendieta, Santiago; Tan, Ken; Christmas, Matthew J.; Olsson, Anna; Vilà, Carles; Wallberg, Andreas; Webster, Matthew T.
Abstract: The eastern honey bee ( Apis cerana ) is of central importance for agriculture in Asia. It has adapted to a wide variety of environmental conditions across its native range in southern and eastern Asia, which includes high‐altitude regions. eastern honey bees inhabiting mountains differ morphologically from neighbouring lowland populations and may also exhibit differences in physiology and behaviour. We compared the genomes of 60 eastern honey bees collected from high and low altitudes in Yunnan and Gansu provinces, China, to infer their evolutionary history and to identify candidate genes that may underlie adaptation to high altitude. Using a combination of F ST ‐based statistics, long‐range haplotype tests and population branch statistics, we identified several regions of the genome that appear to have been under positive selection. These candidate regions were strongly enriched for coding sequences and had high haplotype homozygosity and increased divergence specifically in highland bee populations, suggesting they have been subjected to recent selection in high‐altitude habitats. Candidate loci in these genomic regions included genes related to reproduction and feeding behaviour in honey bees. Functional investigation of these candidate loci is necessary to fully understand the mechanisms of adaptation to high‐altitude habitats in the eastern honey bee.